FORGOTTEN HEROES THE TRUE STORY OF SARAWAK PEOPLE WHO FOUGHT AND DIED ASSISTING ALLIED FORCES IN WWII - Malone, Paul (Strategic Information and Research Development Centre, 2024)
In March 1945 an advance party of Allied special operations forces parachuted into Sarawak's mountains in preparation for a major Allied landing to retake Borneo from the Japanese. Thankfully, the special forces were welcomed by the locals, the highland-dwelling Kelabit people. As the guerrillas moved down-river towards the coast, tribal warriors enthusiastically joined the cause. The locals provided intelligence, engaged in denial of supply operations and finally engaged in an outstandingly successful guerrilla war. There are few accounts of the locals' actions, without whose support the operation could not have succeeded. In 2023 Paul Malone found a trove of documents in the National Archives, (UK) containing the citations for Awards to Civilians for the King's Medal for Courage in the Cause of Freedom. Based on these records, this book recounts the courageous role played by Sarawak people who made the operation a great success. The AIF strategy to retake Borneo by dropping commandos behind enemy lines was a brilliant, but hazardous operation entailing great risk. The risk paid off when former tribes of headhunters took to the Allied forces' side, forming a formidable guerrilla force behind enemy lines. This book highlights the heroic and untold stories of the locals and native tribes in winning the war. The SEMUT special forces' first contact at their drop zone was amongst the Kelabit tribes in Bario, who welcomed them and gave them their undivided support. When the SEMUT operatives moved towards the Japanese lines on the coast, their guerrilla warfare was supported by the local tribes down the Limbang, Lawas, Baram and Rejang rivers. This book provides the documentary backing and proof of the critical role played by Sarawak locals and native tribes during the war.